2016
DOI: 10.1189/jlb.4hi0616-255r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Defects in immune function in patients with sepsis are associated with PD-1 or PD-L1 expression and can be restored by antibodies targeting PD-1 or PD-L1

Abstract: Sepsis is a heterogeneous syndrome comprising a highly diverse and dynamic mixture of hyperinflammatory and compensatory anti-inflammatory immune responses. This immune phenotypic diversity highlights the importance of proper patient selection for treatment with the immunomodulatory drugs that are entering clinical trials. To better understand the serial changes in immunity of critically ill patients and to evaluate the potential efficacy of blocking key inhibitory pathways in sepsis, we undertook a broad phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
161
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(166 citation statements)
references
References 67 publications
4
161
0
1
Order By: Relevance
“…In fact, patients with gastric cancer have a high infiltration of neutrophils in tumours, which show an activated CD54+ phenotype, a high expression of PD‐L1 and were found to suppress normal T‐cell immunity in vitro . These PD‐L1+ neutrophils are also described in sepsis patients . The presence of PD‐L1+ neutrophils is associated with disease progression and the overall survival of gastric cancer or sepsis patients, where the immune suppression could be reversed by blocking PD‐L1 on the activated neutrophils, indicating that the recently developed therapeutics against PD‐1 and PD‐L1 have the potential to neutralize the suppressive activity of MDSCs.…”
Section: Mdsc Activity Of Circulating Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, patients with gastric cancer have a high infiltration of neutrophils in tumours, which show an activated CD54+ phenotype, a high expression of PD‐L1 and were found to suppress normal T‐cell immunity in vitro . These PD‐L1+ neutrophils are also described in sepsis patients . The presence of PD‐L1+ neutrophils is associated with disease progression and the overall survival of gastric cancer or sepsis patients, where the immune suppression could be reversed by blocking PD‐L1 on the activated neutrophils, indicating that the recently developed therapeutics against PD‐1 and PD‐L1 have the potential to neutralize the suppressive activity of MDSCs.…”
Section: Mdsc Activity Of Circulating Neutrophilsmentioning
confidence: 99%
“…No extra stimulus sepsis patients. 61 The presence of PD-L1+ neutrophils is associated with disease progression and the overall survival of gastric cancer or sepsis patients, where the immune suppression could be reversed by blocking PD-L1 on the activated neutrophils, 60,61 indicating that the recently developed therapeutics against PD-1 and PD-L1 have the potential to neutralize the suppressive activity of MDSCs.…”
Section: Relative Precursor Frequency Cd4+ T Cells (%)mentioning
confidence: 99%
“…Thus, our data suggest that blocking the 2B4 signaling pathway may hold promise as a therapeutic target to modulate the immune system and maintain protective immunity in the setting of sepsis. There is precedent for this as therapeutic blockade of PD‐1 and PD‐L1 has been tested in clinical trials to improve immune dysregulation following sepsis . Indeed, we recently showed that pharmacologic blockade of 2B4 reduced sepsis‐induced mortality in a model of CLP .…”
Section: Discussionmentioning
confidence: 99%
“…Work by Young et al (51), using a cecal slurry model, documented that PD-1 gene deficiency also confers a survival advantage in this model of polymicrobial sepsis in neonatal mice. Several studies have also shown a clear role for PD-1 in modulating the geriatric immune response to sepsis (53, 54). …”
Section: Discussionmentioning
confidence: 99%